Pengaruh Implementasi Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kinerja Karyawan - Almeida, Jihan Sri Ayu; Mahdani, Said; Mahdani, Rimal; Rahmazaniati, Linda; Putri, Cut Widy Aulia (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to analyze the effect of implementing the accounting information system and internal control system on employee performance in Islamic banking. The phenomenon of system disruptions and the existence of a research gap in previous studies underlie this study. Data were collected through questionnaires distributed to 24 employees of PT Bank Syariah Indonesia, Meulaboh Branch Office, using a saturated sampling technique and analyzed using multiple linear regression. The results show that the implementation of the accounting information system has a positive and significant effect on employee performance, while the internal control system has no significant partial effect. Simultaneously, both variables have a significant effect on employee performance, with a contribution of 37 percent. These results provide practical implications for Islamic banks to prioritize system integration, user competency development, and technology-based process optimization to improve employee performance sustainability.